First evidence of Ediacaran–Fortunian elliptical body fossils in the Brioverian series of Brittany, NW France. (16th April 2018) - Néraudeau, Didier; Dabard, Marie‐Pierre; El Albani, Abderrazak; Gougeon, Romain; Mazurier, Arnaud; Pierson‐Wickmann, Anne‐Catherine; Poujol, Marc; Saint Martin, Jean‐Paul; Saint Martin, Simona
Abstract : Body fossils are described for the first time from the Upper Brioverian (Ediacaran–Fortunian) deposits of Central Brittany (NW France). The material consists of a dozen of specimens preserved on two slates, recently collected in a quarry in Saint‐Gonlay. The fossils, centimetric in size, have an elliptical and acuminated outline, with a peripheral bulge but without conspicuous concentric or radial lines. These body fossils are preserved in slates that are locally rich in grazing traces, sometimes associated with microbial mats. The sedimentological characteristics of these deposits correspond to a shallow marine shelf environment, with a low to moderate hydrodynamism. Such findings, in concomitance with previous ichnological discoveries, unravel the potential of the Brioverian strata from Brittany as a new locality to provide answers on Ediacaran and early Cambrian biocenoses.